Solitary fibrous tumor of the pleura: 3 case reports - Amorim,Elias (2015)
Summary Introduction: solitary fibrous tumor of the pleura (SFTP) is a rare tumor arising from mesenchymatous cells in submesothelial pleural tissue which, unlike mesothelioma, is not related to asbestos or smoking. Methods: report of four patients who underwent surgical treatment for giant SFTP and review of the pertinent literature. Results: of the four patients operated, two presented symptoms including cough, chest pain and feeling of compression, whereas the other two subjects were asymptomatic. All patients underwent complete surgical resection by wide posterolateral thoracotomy, and surgical specimens removed with minimum bleeding. None of the cases required complementary lobectomy or segmentectomy. All tumors were histologically benign. Conclusion: complete resection of the lesion is the treatment of choice in all SFTP cases. Prognosis of the benign lesion is excellent, although close follow-up is necessary. In the rarer, more aggressive forms, treatment may be complemented by adjunctive chemotherapy or radiotherapy, the benefits of which have yet to be confirmed.